(untitled) (Research, Society and Development, 2021)
Tests were carried out in an open environment with two photovoltaic panels, in the city of Dourados/MS, for six non-consecutive days, between the months of June to July 2018, where one panel was kept original (PV), while the other underwent modifications to operate as a photovoltaic-thermal module using (PVT/w), which is connected to a reservoir for hot water accumulation. The tests were carried out according to the open circuit voltage (Voc), the surface temperature of the photovoltaic cells and the water temperature of the cooling and thermoaccumulation system of the PVT/w, to determine the adequate and adequate thermal energy of the thermal yield. The increase in the temperature of the cooling water negatively affects the value of the open circuit voltage, which was, on average, 2.3% higher for PVT/w, which presented a lower surface temperature in all tests. The average thermal efficiency of PVT/w was 242 W m-2, given in an estimate of total efficiency (thermal and electrical) of 349 W m-2, an increase of 161% in relation to the energy efficiency of PV (only electricity), estimated at 106 W m-2 based on information from the manufacturer’s technical catalog.